Penggunaan Pelat Pengaku Kolom Pada Portal Baja - Supriyatiningsih Supriyatiningsih (Integrated Lab Journal, 2021)
Research on the use of column stiffening plates in the construction of steel portals was carried out in order to determine the effect on loads and deflection. The part of the column that is most prone to failure is in the tensile area, namely the part of the column that is adjacent to the top of the roof beam and in the compression area at the bottom of the roof beam. The tensile part will usually fail to tear while the compressive area occurs when buckling occurs. Tearing and bending failure can be anticipated by installing stiffening plates in the column. Column stiffening plates were varied in the tensile (top), shear (middle), press (bottom), and diagonal areas between the shear-pull areas.The loading is in the form of a concentrated load spread over fourteen points on the roof beam. The loading is carried out in 100 stages (100 sub steps) in order to get a tight iteration so as to get the best results. The optimum model can be determined after testing the five models with variations in the column stiffener plate with the largest load that can be borne by the model. The position of the importance of installing the column stiffener plate can also be found.